# Extensions 1→N→G→Q→1 with N=D6 and Q=C22×S3

Direct product G=N×Q with N=D6 and Q=C22×S3
dρLabelID
S32×C2348S3^2xC2^3288,1040

Semidirect products G=N:Q with N=D6 and Q=C22×S3
extensionφ:Q→Out NdρLabelID
D61(C22×S3) = C2×S3×D12φ: C22×S3/D6C2 ⊆ Out D648D6:1(C2^2xS3)288,951
D62(C22×S3) = C2×D6⋊D6φ: C22×S3/D6C2 ⊆ Out D648D6:2(C2^2xS3)288,952
D63(C22×S3) = S32×D4φ: C22×S3/D6C2 ⊆ Out D6248+D6:3(C2^2xS3)288,958
D64(C22×S3) = C2×Dic3⋊D6φ: C22×S3/D6C2 ⊆ Out D624D6:4(C2^2xS3)288,977
D65(C22×S3) = C22×D6⋊S3φ: C22×S3/C2×C6C2 ⊆ Out D696D6:5(C2^2xS3)288,973
D66(C22×S3) = C22×C3⋊D12φ: C22×S3/C2×C6C2 ⊆ Out D648D6:6(C2^2xS3)288,974
D67(C22×S3) = C2×S3×C3⋊D4φ: C22×S3/C2×C6C2 ⊆ Out D648D6:7(C2^2xS3)288,976

Non-split extensions G=N.Q with N=D6 and Q=C22×S3
extensionφ:Q→Out NdρLabelID
D6.1(C22×S3) = C2×D125S3φ: C22×S3/D6C2 ⊆ Out D696D6.1(C2^2xS3)288,943
D6.2(C22×S3) = C2×D12⋊S3φ: C22×S3/D6C2 ⊆ Out D648D6.2(C2^2xS3)288,944
D6.3(C22×S3) = D12.33D6φ: C22×S3/D6C2 ⊆ Out D6484D6.3(C2^2xS3)288,945
D6.4(C22×S3) = D12.34D6φ: C22×S3/D6C2 ⊆ Out D6484-D6.4(C2^2xS3)288,946
D6.5(C22×S3) = S3×C4○D12φ: C22×S3/D6C2 ⊆ Out D6484D6.5(C2^2xS3)288,953
D6.6(C22×S3) = D1223D6φ: C22×S3/D6C2 ⊆ Out D6244D6.6(C2^2xS3)288,954
D6.7(C22×S3) = D1224D6φ: C22×S3/D6C2 ⊆ Out D6484D6.7(C2^2xS3)288,955
D6.8(C22×S3) = D1227D6φ: C22×S3/D6C2 ⊆ Out D6244+D6.8(C2^2xS3)288,956
D6.9(C22×S3) = Dic6.24D6φ: C22×S3/D6C2 ⊆ Out D6488-D6.9(C2^2xS3)288,957
D6.10(C22×S3) = S3×D42S3φ: C22×S3/D6C2 ⊆ Out D6488-D6.10(C2^2xS3)288,959
D6.11(C22×S3) = Dic612D6φ: C22×S3/D6C2 ⊆ Out D6248+D6.11(C2^2xS3)288,960
D6.12(C22×S3) = D1213D6φ: C22×S3/D6C2 ⊆ Out D6248+D6.12(C2^2xS3)288,962
D6.13(C22×S3) = S3×Q83S3φ: C22×S3/D6C2 ⊆ Out D6488+D6.13(C2^2xS3)288,966
D6.14(C22×S3) = D1215D6φ: C22×S3/D6C2 ⊆ Out D6488-D6.14(C2^2xS3)288,967
D6.15(C22×S3) = D1216D6φ: C22×S3/D6C2 ⊆ Out D6488+D6.15(C2^2xS3)288,968
D6.16(C22×S3) = C2×D6.3D6φ: C22×S3/D6C2 ⊆ Out D648D6.16(C2^2xS3)288,970
D6.17(C22×S3) = C2×D6.4D6φ: C22×S3/D6C2 ⊆ Out D648D6.17(C2^2xS3)288,971
D6.18(C22×S3) = C32⋊2+ 1+4φ: C22×S3/D6C2 ⊆ Out D6244D6.18(C2^2xS3)288,978
D6.19(C22×S3) = C2×D6.D6φ: C22×S3/C2×C6C2 ⊆ Out D648D6.19(C2^2xS3)288,948
D6.20(C22×S3) = C2×D6.6D6φ: C22×S3/C2×C6C2 ⊆ Out D648D6.20(C2^2xS3)288,949
D6.21(C22×S3) = D1212D6φ: C22×S3/C2×C6C2 ⊆ Out D6488-D6.21(C2^2xS3)288,961
D6.22(C22×S3) = D12.25D6φ: C22×S3/C2×C6C2 ⊆ Out D6488-D6.22(C2^2xS3)288,963
D6.23(C22×S3) = Dic6.26D6φ: C22×S3/C2×C6C2 ⊆ Out D6488+D6.23(C2^2xS3)288,964
D6.24(C22×S3) = C2×S3×Dic6φ: trivial image96D6.24(C2^2xS3)288,942
D6.25(C22×S3) = S32×C2×C4φ: trivial image48D6.25(C2^2xS3)288,950
D6.26(C22×S3) = S32×Q8φ: trivial image488-D6.26(C2^2xS3)288,965
D6.27(C22×S3) = C22×S3×Dic3φ: trivial image96D6.27(C2^2xS3)288,969

׿
×
𝔽